Original articleSpatial relationships between diffuse prion protein deposits and neuronal perikarya in variant Creutzfeldt-Jakob disease - A. Armstrong, Richard (Folia Neuropathologica, 2013)
Two morphological types of prion protein (PrPsc) deposit occur in the cerebral cortex of cases of variant Creutzfeldt-Jakob disease (vCJD), viz., diffuse and florid deposits. The objective of this study was to determine whether diffuse-type PrPsc deposits in areas of the cerebral cortex in six cases of the variant form of CJD (vCJD) were spatially correlated with neurons and whether diffuse deposit size was related to the number of adjacent neurons contributing PrPsc. In cortical gyri, density of surviving neurons was 5.38-12.15 per 50 × 200 µm sample field, neurons being distributed randomly, regularly or were clustered relative to the pia mater. Density of neurons embedded within diffuse deposits, however, was three to eight times their overall density in the section. In addition, diffuse deposit area was positively correlated with the number of embedded neurons. The frequency distribution of diffuse deposits with 0, 1, 2, 3, …, n, embedded neurons did not deviate from a Poisson distribution. These results suggest: (1) diffuse deposits in vCJD develop in situ as a result of the formation of PrPsc in relation to clusters of neurons, (2) size of a diffuse deposit is determined by the number of adjacent neurons which develop PrPsc, and (3) the probability that PrPsc is formed in relation to one neuron is independent of that of its neighbour.